Textbook of hyperbaric medicine - Jain, K. K. (Kewal K.) (Hogrefe, 2009)
This textbook, now appearing in its 5th, fully updated, and expanded edition, has become widely recognized as the best exposition available on the topic of hyperbaric medicine and the wide range of applications of hyperbaric oxygen (HBO). In addition to explaining the basic principles of HBO therapy, and its application in carbon monoxide poisoning and decompression sickness, the textbook looks objectively and critically at its use in numerous other areas, such as stroke, neurological disorders, traumatology and wound healing, infectious diseases, rehabilitation and sports medicine, plastic surgery, emergency medicine, ophthalmology, obstetrics, pediatrics, organ transplantation, and as an adjunct to the treatment cancer. With over 2000 up-to-date references and an extensive index, the volume is not just a textbook suitable for those seeking an introduction to this expanding field but also an invaluable resource for specialists. Also included is a chapter on hyperbaric medicine as a specialty, with recommendations on training, practice, and research. Worldwide review of hyperbaric facilities indicates considerable progress and expansion of use of HBO in the United States.